Indigenous Method of Acetone Recycling - Manjunatha, K.; Prasad, R. V.; Jamuna, K. V.; Ramkrishna, V.; D’souza, Placid E.; Rao, Suguna (Indian Journal of Veterinary Anatomy, 2015)
The present study was conduced to recycle the used acetone from the plastination process by using an indigenously designed acetone recycling unit. Either alcohol or cold acetone are commonly used as a dehydrant for plastination. Acetone is usually the best solvent for dehydration. An accumulation of waste acetone during plastination (contaminated with water and fats) necessitates not only the purchase of new acetone and also the disposal of the old acetone is a problem as it is a hazardous waste. In the present study, the purity of the recycled acetone was 99%. The instrument designed was very handy and needed very less investment as it does notinvolve any sophisticated instruments.